Desarrollo de un desengrasante biodegradable a partir del aprovechamiento de desechos orgánicos de la corteza de naranja. (Citrus sinensis) (2021)
This project seeks to replace the ethoxylated nonyl substance as a raw material for industrial degreasers due to its high environmental impact and harmfulness, which has generated a significant decrease in its production and worldwide commercialization. This situation impacts the Colombian company Asenix S.A, which is looking for an economically viable alternative to replace said compound. For this reason, the main objective is to develop a degreaser with biodegradable properties, where one of the main raw materials is orange essential oil, which is obtained by the hydrodistillation method of orange peel (Citrus sinensis). For the experimental development, a bibliographic review is carried out in order to establish the appropriate parameters for the extraction of the orange EA. A gas chromatography of the EA extracted in the experimentation is carried out in order to know the composition and / or presence of the monoterpene D-Limonene.